Improving Access to Jobs and Earnings Opportunities : The Role of Activation and Graduation Policies in Developing Countries - Almeida, Rita; Arbelaez, Juliana; Honorati, Maddalena; Kuddo, Arvo; Lohmann, Tanja; Ovadiya, Mirey; Pop, Lucian; Sanchez Puerta, Maria Laura; Weber, Michael (World Bank, Washington, DC, 2013)
Throughout the developing world there is a growing demand for advice on the design of policies to facilitate access of the most vulnerable individuals to jobs, while reducing their dependency from public income support schemes. Even though these policies are common to both the activation and graduation agendas, a separation is needed as the graduation of beneficiaries out of poverty is a much more ambitious agenda. This paper proposes a simple policy framework highlighting the most common barriers for productive employment. It also reviews the topic of incentive compatibility of income support schemes and employment support programs that are used to address them. The paper finds that, especially in middle income countries, activation and active labor market programs play an important role connecting individuals to jobs and improving earnings opportunities. In low income countries, these programs are far from being a panacea to graduate beneficiaries out of poverty. Furthermore, only scant evidence is available on the pathways to graduation and significant knowledge gaps remain. More cross-disciplinary research is needed to strengthen the evidence base and develop recommendations for different contexts and capacity levels.